Estrategias didácticas para el mejoramiento de la motricidad fina en los niños(as) de 5 a 6 años de la Unidad Educativa Taisha - Ramos Meneses, Jessica Marlin (2023)
XII ABSTRACT The present research aims to apply proposed didactic strategies to improve fine motor skills in children aged 5 to 6 years at Taisha Educational Unit through an educational intervention. A mixed research approach was employed, utilizing two instruments to collect information: an observation checklist administered to a group of 60 children aged 5 to 6 years at Taisha Educational Unit, and an open-ended questionnaire administered to two teachers at the institution. The results indicated that teachers are familiar with appropriate strategies for the development of fine motor skills, and the majority of children have initiated the process of developing these skills. A proposal consisting of 10 workshops was designed, incorporating activities to enhance fine motor skills through techniques such as brain gym exercises, my artwork, rainbow colors, crawl, marathon, crazy hair salon others. A significant improvement in fine motor skills was observed in children after the implementation of this strategy. It is concluded that this proposal can serve as a model for other educational institutions seeking to enhance the development of fine motor skills in preschool-age children.